PEMBERDAYAAN IBU BALITA DALAM OPTIMALISASI PERTUMBUHAN DAN PERKEMBANGAN BALITA MELALUI PEMANFAATAN APLIKASI e-POSYANDU KESEHATAN (ePoK) DI KELURAHAN KAMPUNG BUGIS KOTA TANJUNGPINANG - Melly Damayanti; Darwitri, Darwitri; Nurul Aini Suria Saputri; Rawdatul Jannah (Bajang Institute, 2024)
The early childhood period is a phase of very rapid growth and development, including physical growth, psychomotor development, mental, and social development. At this age, children increasingly develop their thinking, speaking, sensory perception, and motor skills. The role of parents, especially mothers, is crucial in monitoring and stimulating the growth and development of toddlers. The goal of this community service project wais to empower mothers of toddlers to optimize their children’s growth and development through the use of the ePoK application in the Work Area of the Community Health Center of Kampung Bugis in 2024. The target group for this activity consists of mothers and their toddlers experiencing growth and developmental issues in the Kampung Bugis neighborhood of Tanjungpinang City, totaling 35 individuals. The methods used include preparation, early detection of growth and development issues, counseling and stimulation training, monitoring, assistance, and evaluation. The results showed an increase in mothers' knowledge and skills in providing stimulation, along with improvements in the growth and development status of the toddlers. Specifically, 85,7% of mothers had high knowledge, and 82,9% had good skills. The percentage of toddlers with normal growth status increased by 51,4%, while those with appropriate developmental status rose to 88,63%